Architecture for the Commons. Participatory Systems in the Age of Platforms. - Sanchez, Jose (Routledge, 2020)
Architecture for the Commons dives into an analysis of how the tectonics of a building is fundamentally linked to the economic organizations that allow them to exist. By tracing the origins and promises of current technological practices in design, the book provides an alternative path, one that reconsiders the means of achieving complexity through combinatorial strategies. This move requires reconsidering serial production with crowdsourcing and user content in mind. The ideas presented will be explored through the design research developed within Plethora Project, a design practice that explores the use of video game interfaces as a mechanism for participation and user design. The research work presented throughout the book seeks to align with a larger project that is currently taking place in many different fields: The Construction of the Commons. By developing both the ideological and physical infrastructure, the project of the Commons has become an antidote to current economic practices that perpetuate inequality. The mechanisms of the production and governance of the Commons are discussed, inviting the reader to get involved and participate in the discussion. The current political and economic landscape calls for a reformulation of our current economic practices and alternative value systems that challenge the current market monopolies. The book connects principles of architecture, economics and social sciences to provide alternatives to the current production trends.
Keywords: Architektur; Stadtentwicklungsplanung; Bauproduktion; Entwurfsprozess; Digitalisierung; Kommunikationstechnologie; Partizipation; Kooperation; Gemeinwohl; Zivilgesellschaft; Wirtschaftssystem; Crowdsourcing; Commons; Gemeingut